2007
DOI: 10.1109/tpami.2007.1019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Biometric Quality Measures

Abstract: We document methods for the quantitative evaluation of systems that produce a scalar summary of a biometric sample's quality. We are motivated by a need to test claims that quality measures are predictive of matching performance. We regard a quality measurement algorithm as a black box that converts an input sample to an output scalar. We evaluate it by quantifying the association between those values and observed matching results. We advance detection error trade-off and error versus reject characteristics as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
225
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(225 citation statements)
references
References 11 publications
0
225
0
Order By: Relevance
“…Results showed superiority of the action-based method proposed in this paper over the histogram-based method proposed in [1]. Furthermore, evaluation showed a significant improvement in the verification accuracy when using the newly introduced features.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Results showed superiority of the action-based method proposed in this paper over the histogram-based method proposed in [1]. Furthermore, evaluation showed a significant improvement in the verification accuracy when using the newly introduced features.…”
Section: Discussionmentioning
confidence: 72%
“…Equal error rates (ERRs) of 0.007 and 0.002 were achieved for 100 and 200 mouse-strokes, respectively. Ahmed et al [1] monitored the mouse activity of users while they performed their daily tasks within their own chosen operating conditions and applications. Features were extracted and aggregated into histograms that were used to characterize each user.…”
Section: Mouse-based User Verification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. Grother et al [1] reported that quality measures predict the authentication performance, and Y. Chen et al [2] proposed two such quality measures. K. Kryszczuk et al [3] reported a method in which classifier decisions and the corresponding reliability information are combined to predict and correct verification decisions.…”
mentioning
confidence: 99%